Multilayer architecture microfluidic network array for combinatorial drug testing on 3D-cultured cells. (4th June 2019) - Chang, Hao-Chen; Lin, Ching-Hui; Juang, Duane; Wu, Huei-Wen; Lee, Che-Yen; Chen, Chihchen; Hsu, Chia-Hsien
Abstract: In vitro testing of drug compounds on cell models during the drug development process represents an indispensable step in the initial screening process. Although drug testing on three-dimensional (3D) cultured cells may provide a more accurate prediction of drug efficacy, it is relatively costly and time-consuming to perform compared with conventional 2D cultures due to the thick z -axis of the 3D models. In this study, we have presented a microfluidic platform with integrated pneumatic valves for producing a thin-gel 3D cell culture-based combinatorial drug screening array (3D- μ CDS array). The multilayer architecture and microfluidic layout has a smaller device footprint than a single-layer microfluidic channel arrangement, making it well suited to scaling up for high-throughput combinatorial drug screening on 3D cell model. We performed 8 × 8 combination drug screening experiments with the device using two anti-cancer drugs (doxorubicin and paclitaxel) on MDA-MB-231 and MCF-7 breast cancer cell lines for demonstration. Our results indicate that our 3D- μ CDS array device allows the successful screening of multiple drug combinations while reducing the operation time and the number of sample/reagents required, making it an ideal tool for general combinatorial drug screening, as well as for applications using valuable tissues and clinical samples.